Optimizing CaO-based CO2 adsorption: Impact of operating parameters - Chengzhuang Zhang; Jia Fang; Zhiqiang Han; Peng Chen; Xilong Xu; Kejian Wang; Yunxi Shi; Jianxiong Liao (iScience)
Summary: CaO-based adsorbents present a promising approach for industrial CO2 emissions reduction. This study systematically investigates the influence of adsorption temperature, adsorbent mass, CO2 concentration, and flow rate on CO2 capture efficiency using commercial CaO via thermogravimetric analysis (TGA). Optimal adsorption performance, achieving a capacity of 0.62 g/g and a rate exceeding 0.14 g/g/min, was observed at 750°C, 7 mg mass, 20% CO2, and 20 mL/min flow. Characterization (SEM, BET, and FTIR) indicated that 750°C preserved a hierarchical pore structure (24.64 m2/g surface area, 0.1026 cm3/g pore volume, and 7.08 nm average pore size), mitigating sintering and pore blockage while confining carbonation to surface layers. Kinetic modeling confirmed chemisorption dominance (pseudo-second-order). These findings elucidate fundamental mass/heat transfer limitations, supporting the development of enhanced CaO-based carbon capture, utilization, and storage (CCUS) technologies.